A population physiologically‐based pharmacokinetic model to characterize antibody disposition in pediatrics and evaluation of the model using infliximab. Issue 1 (19th July 2021) - Chang, Hsuan Ping; Shakhnovich, Valentina; Frymoyer, Adam; Funk, Ryan Sol; Becker, Mara L.; Park, K. T.; Shah, Dhaval K.
Abstract : Aims: In order to better predict the pharmacokinetics (PK) of antibodies in children, and to facilitate dose optimization of antibodies in paediatric patients, there is a need to develop systems PK models that integrate ontogeny‐related changes in human physiological parameters. Methods: A population‐based physiological‐based PK (PBPK) model to characterize antibody PK in paediatrics has been developed, by incorporating age‐related changes in body weight, organ weight, organ blood flow rate and interstitial volumes in a previously published platform model. The model was further used to perform Monte Carlo simulations to investigate clearance vs . age and dose–exposure relationships for infliximab. Results: By estimating only one parameter and associated interindividual variability, the model was able to characterize clinical PK of infliximab from two paediatric cohorts ( n  = 141, 4–19 years) reasonably well. Model simulations demonstrated that only 50% of children reached desired trough concentrations when receiving FDA‐labelled dosing regimen for infliximab, suggesting that higher doses and/or more frequent dosing are needed to achieve target trough concentrations of this antibody. Conclusion: The paediatric PBPK model presented here can serve as a framework to characterize the PK of antibodies in paediatric patients. The model can also be applied to other protein therapeutics to advance precision medicine paradigm and optimize antibody dosing regimens in children.